Attitude of women towards family planning in selected rural communities of Ibadan (2012)
The immediate need to control the high fertility rates among women in the rural part of Nigeria has attracted the interest of scholars in the academic world. Lots have been done by international agencies and other stakeholders to encourage the use of family planning methods among women both in rural and urban areas of developing countries including Nigeria. This notwithstanding, there still exist a great challenge of unmet needs regarding family planning especially in the rural part of Ibadan as the desired altitudinal and behavioral changes towards family planning Is yet to be achieved. This study attempts to examine the attitude of women from selected rural areas in Ibadan towards family planning using the Health Belief Model and Social Action as frameworks for explanation. The qualitative and quantitative methods of research were employed with a survey of 136 randomly selected mothers from 5 rural communities in Ibadan, 15 IDT. 5 Klls and 5 FGDs. The Statistical Package for Social Sciences was utilized in analyzing the quantitative data, while the qualitative data were analyzed using content analysis. The study revealed that the socio-economic status of mothers significantly influenced their attitude towards family planning. Most of the women had only primary education and more women had no formal education compared to those who had secondary and tertiary education, hence few of them displayed positive attitude towards family planning methods. Majority of the women hardly gave birth in hospitals and depended on their husbands to decide what ever method will be used to space or limit the number of children they will have. The study also revealed that women perceived benefits of family planning as measures: to control population, reduce infant and maternal mortality and also make mothers healthy and strong after child birth. However, these were learnt after they had given birth to more than four children in other places aside the hospitals. The study recommends that couples in rural areas be encouraged to make effective use of contraceptives and adequately educated to appreciate the essence of utilizing family planning methods in order to give birth to quality children. Ante-natal and delivery cost should be highly subsidized in rural areas for women to be encouraged to give birth in the hospitals from the very first child and learn about, family planning methods. It was also recommended that family planning programmes that will attract